Optimasi Konsentrasi Minyak Atsiri Biji Pala (Myristica fragrans) Dan Sereh Wangi (Cymbopogon nardus L.) Sebagai Sediaan Repellent Patch Dengan Metode Simplex Lattice Design - Ananda Natasya; Mutmainnah; Amran Nur (Media Farmasi, 2026)
Introduction: Mosquitoes can transmit various diseases such as dengue fever, malaria, and filariasis. DEET (N,N-Diethyl-meta-Toluamide) is commonly used as a repellent, but it has the potential to cause irritation. Essential oils from various plants have high efficacy as mosquito repellents, such as nutmeg essential oil(Myristica fragrans) with 20% efficacy and lemongrass essential oil (Cymbopogon nardus L.) with 10% efficacy. Both of these essential oils can be formulated into repellent patches, a practical adhesive formulation that slowly releases the active ingredients. Formula optimization was conducted using the Simplex Lattice Design (SLD) method to obtainthe best combination. Objectives: To investigate the optimum concentration of nutmeg and citronella essential oil as repellent patch preparation using Simplex Lattice Design method. Method: This study is an experimental study. Samples were obtained from the market and then formulated using the SLD method, where the concentration of essential oils ranged from 0-20%. After that, patch preparations were made, and the resulting preparations were then evaluated to assess characteristics including organoleptic testing, pH, effectiveness, weight uniformity, patch thickness, fold resistance, moisture content, irritation test, and hedonic test. The responses were then re-entered into the SLD, and the optimal value was determined based on the desirability value obtained. Results: The test results meet the requirements, with the following data obtained: in the organoleptic test, it has a yellowish-white color, with an essential oil aroma and smooth texture, pH 5.7-6.86, weight uniformity 0.342-0.459 g, thickness of 0.6–1.00 mm, fold resistance >200, moisture content of 5.88–8.33%, irritation (–), the most preferred hedonic formulas being 1 and 3, and a reaction time ranging from 3.5 to 4 hours. Conclusion: The repellency result obtained was 4 hours and the optimum concentration in formula 1 (0:20%) with a desirability value of 0.872.